Bacteriological profile and variables related to neoplastic wound in patient under palliative care: cross-sectional study (Research, Society and Development, 2020)
Objective: to verify the association between bacteriological profile and variables related to neoplastic wounds of patients under palliative care. Method: Cross-sectional study, with a sample composed of 36 patients admitted to the wards of the National Cancer Institute José Alencar Gomes da Silva - Unit IV. Data collection took place between the months of October and December 2018, using a specific form. In the data analysis, descriptive measures and Fischer/chi-square test were used at the 5% significance level (α = 0.05). Results: The sample was composed by 36 individuals, 19 (52.78%) of whom were female, with a predominant percentage of metastasis formation (63.89%). There is a strong association between the variables palliative radiotherapy and the presence of Pseudomonas sp. (p = 0.02), type of primary tumor and the presence of Citrobacter sp. and Acinetobacter sp. (p